Sosialisasi dan Pendampingan Pola Asuh Anak Wanita Karir di Perum Citra Permata Sakinah Purwakarta : Sosialisasi dan Pendampingan - Melinda Maulani; Nur Aeni Muhfi; Sofia Gussevi (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
This service activity is motivated by the researcher's observations regarding career women who leave their children to their parents (grandmothers/grandparents) and there are also those who hand over the care of their children to people who actually lack knowledge in parenting. Indeed, not all career women fail in their role as mothers, but the application of parenting in the childcare process is sometimes inappropriate. Actually, both career women and housewives will be successful in raising children if they choose and apply the right parenting pattern. Based on this, this activity aims to provide socialization about child care patterns applied by career women by providing assistance to several families at Perum Citra Permata Sakinah Purwakarta. The results of this activity showed that juvenile delinquency had occurred due to the application of inappropriate parenting. The efforts that have been made in this activity are in the form of deliberation between husband and wife in child care so that undesirable things do not happen to their children.